Sirhindi's criticism of the Wahdat al-Wujud in Ibn 'Arabi course - Nunu Burhanuddin (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article describes Sirhindi's critique of the Wahdat al-Wujud Ibn 'Arabi concept. The method used is the content analysis based on the book Al-Maktubat li-al-Imam al-Alim al-Robbani al-Mujaddid al-Sirhindi. The results of the study state that, first, Ibn 'Arabi's view of the universe as imagination clashes with the concept of creation which calls God the Creator. The mention of the concept of creation is considered very important because this idea can direct humans to the concept of retribution and punishment. Second, the experience of fana’' and baqa’' does not mean involvement in the divine life, but is like a dream state, like a dream of becoming a king who in reality is not a king. Third, Maqam 'abdiyyah (servitude) as the highest level among the other three stages, namely the unity of Essence (Wahdat al-Wujud), shadow (dzilliyat), and servanthood ('abdiyyat). The mention of the three stages is intended to show the truth about the Supreme Godhead, as well as mystical criticism to the Sufis which starts from the first stage (al-jam') and then stops at the second stage (farq ba'da al-jam'), and not paying attention to the stages of slavery, which asserts that God is very different from creatures. Fourth, Sirhindi's critique of Wahdat al-Wujud is complemented by the submission of the concept of Wahdat al-Shuhud which is based on the highest Sufi experience of divine transcendence by the teachings of the Prophets. Thus, the world is not one with God, nor is it in his form. God is one Essence, and the world is another in which the two will have nothing in common.